2008
DOI: 10.1086/588462
|View full text |Cite
|
Sign up to set email alerts
|

Another Nonsegregated Blue Straggler Population in a Globular Cluster: the Case of NGC 2419

Abstract: We have used a combination of ACS HST high-resolution and wide-field Subaru data in order to study the blue straggler star ( BSS) population over the entire extension of the remote Galactic globular cluster NGC 2419. The BSS population presented here is among the largest ever observed in any stellar system, with more than 230 BSSs in the brightest portion of the sequence. The radial distribution of the selected BSSs is essentially the same as that of the other cluster stars. In this sense the BSS radial distri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
90
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 50 publications
13
90
0
Order By: Relevance
“…Table 4 lists the values of Γ MST and the related 1σ uncertainties computed for the BSS populations in the four target clusters, and, for comparison, for NGC 2419 and Pal 14. In agreement with the results of Dalessandro et al (2008) and Beccari et al (2011), we find that BSS and RGB stars share the same radial distribution in NGC 2419 and Pal 14 (Γ MST 1). Conversely, BSSs appear to be significantly more segregated than giant stars in the other four GCs.…”
Section: The Minimum Spanning Treesupporting
confidence: 92%
“…Table 4 lists the values of Γ MST and the related 1σ uncertainties computed for the BSS populations in the four target clusters, and, for comparison, for NGC 2419 and Pal 14. In agreement with the results of Dalessandro et al (2008) and Beccari et al (2011), we find that BSS and RGB stars share the same radial distribution in NGC 2419 and Pal 14 (Γ MST 1). Conversely, BSSs appear to be significantly more segregated than giant stars in the other four GCs.…”
Section: The Minimum Spanning Treesupporting
confidence: 92%
“…In a few other GCs (see, for example, NGC 1904 and M75;Lanzoni et al 2007b;Contreras Ramos et al 2012, respectively) the radial distribution shows a clear central peak but no upturn in the external cluster regions. In the case of ω Centauri (Ferraro et al 2006b), NGC 2419 (Dalessandro et al 2008), and Palomar 14 ) the BSS radial distribution is flat all over the entire cluster extension. Since BSSs are more massive than the average cluster stars (and therefore suffer from the effects of dynamical friction), these different observed shapes have been interpreted as due to different "dynamical ages" of the host clusters (Ferraro et al 2012, hereafter F12): a flat BSS distribution is found in dynamically young GCs (Family I), where two-body relaxation has been ineffective in establishing energy equipartition in a Hubble time and dynamical friction has not segregated the BSS population yet.…”
Section: Introductionmentioning
confidence: 91%
“…The standard photometric analysis (see Dalessandro et al 2008aDalessandro et al , 2008b) has been performed on the "flt" images, which are corrected for flat field, bias, and dark counts. These images have been further corrected for "Pixel-area-map" 6 with standard IRAF procedures.…”
Section: Observations and Data Analysismentioning
confidence: 99%